Reconciling a Fresh Start with Personal Data: The Challenge of EU Insolvency Discharge - Bolzanas Darius; Jokubauskas Remigijus (Baltic Journal of Law & Politics)
Designed to provide a fresh start, the discharge procedure relieves debtors of pre-bankruptcy debts, allowing them to resume economic activity. Attainment of this aim is also linked with the processing of the debtor’s personal data during and even after the discharge procedure is completed. The processing of the debtor’s personal data in the discharge procedure is subject to the general rules of protection of personal data in the European Union law. This article analyzes what the legal basis for processing of debtor’s personal data is during and after the discharge procedure. It also deals with the question whether a proper balance between the principle of publicity of the discharge procedure and the main goals of the processing of personal data (lawful processing of personal data, data minimization principle) are achieved under the current legal framework of the European Union. To show the practical problems in this area, the article focuses on the recent case law of the Court of Justice of the European Union, which reveals the problems to achieve the proper balance between the different aims of the discharge of debt procedure and processing of personal data.